Strengthening inflation targeting: Review and renewal processes in Canada and other advanced jurisdictions - Robert A. Amano; Thomas J. Carter; Lawrence Schembri (Bank of Canada, 2020)
A growing number of advanced economies with monetary policy frameworks that involve inflation targeting have adopted formal processes of review and renewal. These allow policy-makers and other stakeholders to assess the current framework's performance to date, explore the merits of potential alternative frameworks and reach decisions about how best to enhance design and implementation. In this paper, we argue that well-governed review and renewal processes can contribute importantly to the success of a monetary policy framework: (1) they help to adjust the framework in response to experience, theoretical developments and changes in the economy; and (2) they enhance the legitimacy and credibility of changes made to the framework. However, as these processes involve inputs from the government or legislature, they also create potential for tensions regarding central bank independence. We use an international comparison to show that these considerations have been balanced in different ways across countries and time, with a spectrum running from relatively technocratic processes to ones more closely linked to the political cycle. We also highlight several unique aspects of the modern review and renewal experience in Canada, where renewals of the Bank of Canada's joint inflation-control agreement with the government have regularly been preceded by in-depth framework reviews, each involving a large amount of original research and significant levels of transparency.
Keywords: E52; E58; 330; Monetary policy framework; Central bank research; Inflation targets